Economic Downturns and the Determination of Portfolio Asset Allocation - Syed Mohd Na'im, Syed Salim (2011)
A most common question in finance, particularly in investment perspective, is how an investor should allocate his wealth. Robert C. Merton (1975) remarks that the quest for an answer to the problem of lifetime consumption and portfolio selection under uncertainty is the beginning point for the development of a theory of Finance. This research looks into the possibility of forming effective/profitable portfolio asset allocation during economic downturns which occurred in the period between year 1993 and 2008. We employ out-of-sample forecasting techniques using time-varying factors of constants (alpha) and asset sensitivities (beta) over the market and covariance/correlation in asset allocation. In addition, we also investigate if economic indicators have had any effect on forming asset allocation, particularly the stock markets. It is found that out of 24 portfolio asset allocation strategies investigated; two strategies provide superior return over risk results. The research also reveals that the incorporation of economic indicators has improved our model significantly. This research contributes to the present literature through recommendations for achieving better portfolio’s return forecasts. It is intended that the findings will strengthen the practicability of Markowitz’s Mean Variance theory and Sharpe’s and Lintner’s Capital Asset Pricing Model. We have proven that both models are feasible with some innovative adjustments made to them.